The Determinant of Banking Efficiency (Data Envelopment Analysis Based on Intermediation Approach) - Zahra, Nabila; Darwanto, Darwanto (Muhammadiyah University Press, 2019)
This research aims at analyzing the level of efficiency with intermediation approach and determinant of efficiency of Bank Pembangunan Daerah (BPD). Efficiency is measured using the Data Envelopment Analysis (DEA) method based on the intermediation approach. This research contribute on modelling of determinant of efficiency of Bank Pembangunan Daerah (BPD) using intermediation approach. The object of this research is 26 BPD(s). Furthermore, the determinant of efficiency of BPD is analyzed using the Tobit regression. The level of efficiency is the dependent variable. Meanwhile, the independent variables used are CAR, LDR, NPL, NIM, ROA, Inflation, Economic Growth, and Interest Rate. The research results show that BPD has a different efficiency level average (high, sufficient, moderate, and low efficiency level average). This is due to the use of inputs that have an impact on the optimal output maximization. CAR and LDR have the significant and positive effects on the efficiency of BPD. Interest rate and inflation have the significant and negative effects on the efficiency of BPD. Meanwhile, NPL, NIM, ROA and Economic Growth have no effects on the efficiency of BPD. This results is expected to contribute in identifying any factor affecting the efficiency of BPD, both the internal and macro economy, and also to be the stimulus for the development of health measuring instrument of BPD in which efficiency reflects the quality of risk management on the intermediary activity of BPD.